PEMBAGIAN BEBAN VLAN PADA IPV6 HSRP - Daniel Halomoan Saragi Napitu; Nicodemus Firman River Hutabarat; Waldemar Banurea (STMIK KAPUTAMA, 2022)
Hot Standby Router Protocol (HSRP) is a Cisco propreitary protocol for setting a redundant gateway, to support a high availability network. When there is fault in one of the gateway (the active gateway), the passive gateway will take the active function. All VLAN will migrate from the active to passive gateway. This aim of this research is to analyze the VLAN load balancing , to optimize the migration process. This research will also use the IPv6 as the logical addressing